The Influence of Tax Understanding, System Modernization, and Love of Money Attitudes on Tax Evasion among Individual Taxpayers Registered at KPP Pratama Cibitung - Fadila, Yona; Wulandari, Siska (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to understand the extent to which taxation understanding, the level of tax system modernization, and attitudes toward money influence taxpayers' tendency to engage in tax evasion. This quantitative descriptive research method utilizes a data collection approach based on questionnaires distributed online via Google Forms to taxpayers registered at KPP Pratama Cibitung. A total of 100 responses were obtained from the questionnaire distribution. Subsequently, the questionnaire data were analyzed using t-tests and multiple linear regression using SPSS version 26.0 to ascertain their impacts. This study reveals that taxation understanding, system modernization, and love of money attitudes positively influence tax evasion actions conducted by individual taxpayers registered at KPP Pratama Cibitung. The tax authorities need to enhance education programs on the taxation system for taxpayers, focusing on understanding tax obligations and their consequences. Despite the modernization of the tax administration system, tax authorities need to continue innovating to improve its effectiveness. Further evaluation of the existing system may be necessary to identify areas that can be enhanced or improved. Additionally, introducing new features that can make tax evasion practices more difficult may also be necessary.